Early Appropriate Care: A Protocol to Standardize Resuscitation Assessment and to Expedite Fracture Care Reduces Hospital Stay and Enhances Revenue. Issue 6 (June 2016) - Vallier, Heather A.; Dolenc, Andrea J.; Moore, Timothy A.
Abstract : Objectives: We hypothesized that a standardized protocol for fracture care would enhance revenue by reducing complications and length of stay. Design: Prospective consecutive series. Setting: Level 1 trauma center. Patients/Participants: Two hundread and fifty-three adult patients with a mean age of 40.7 years and mean Injury Severity Score of 26.0. Intervention: Femur, pelvis, or spine fractures treated surgically. Main Outcome Measurements: Hospital and professional charges and collections were analyzed. Fixation was defined as early (<36 hours) or delayed. Complications and hospital stay were recorded. Results: Mean charges were US 180, 145 with a mean of US 66, 871 collected (37%). The revenue multiplier was US 59, 882/6989 (8.57), indicating hospital collection of US 8.57 for every professional dollar, less than half of which went to orthopaedic surgeons. Delayed fracture care was associated with more intensive care unit (4.5 vs. 9.4) and total hospital days (9.4 vs. 15.3), with mean loss of actual revenue US 6380/patient delayed (n = 47), because of the costs of longer length of stay. Complications were associated with the highest expenses: mean of US 291, 846 charges and US 101, 005 collections, with facility collections decreased by 5.1%. An uncomplicated course of care was associated with the most favorable total collections: (US 60, 017/158, 454 = 38%) and the shortest mean stay (8.7 days). Conclusions: Facility collections were nearly 9 times more than professional collections. Delayed fixation was associated with more complications, and facility collections decreased 5% with a complication. Furthermore, delayed fixation was associated with longer hospital stay, accounting for US 300K more in actual costs during the study. A standardized protocol to expedite definitive fixation enhances the profitability of the trauma service line. Level of Evidence: Economic Level IV. See Instructions for Authors for a complete description of levels of evidence.